FRACTIONATION OF PHYTOHEMAGGLUTININ, I. PURIFICATION OF THE RNA AND DNA SYNTHESIS-STIMULATING SUBSTANCES AND EVIDENCE THAT THEY ARE NOT PROTEINS - Goldberg, M. L. (1969)
We have separated the RNA synthesis-stimulating activity and the DNA synthesis-stimulating activity of extracts of Phaseolus vulgaris (phytohemagglutinin) from the erythroagglutinins, leukoagglutinins, and cytotoxic factors. We have shown that the substances stimulating the synthesis of nucleic acids are probably not proteins, since they are not significantly affected by rigorous deproteinization or treatment by trypsin and pronase. Likewise, they do not appear to be nucleic acids, since they are not precipitated by perchloric acid and resist RNase, DNase, and phosphodiesterases. They are probably not carbohydrates, since 98 per cent of the carbohydrate can be removed from a preparation with only a moderate loss in activity. The RNA and DNA synthesis-stimulating activities are probably associated with separate molecules, since they are destroyed by periodate at different rates.